Updates in Sterilization Techniques in Operative Theatre (The Review of Diabetic Studies, 2026)
Maintaining a sterile environment in operative theatres is crucial for minimizing the risk of healthcare-associated infections (HAIs), which can lead to prolonged recovery, increased healthcare costs, and significant morbidity or mortality. This study explores the historical evolution of sterilization methods, assesses current standards and guidelines, and identifies challenges faced in sterilization processes. Historically, sterilization techniques have transitioned from rudimentary practices, such as boiling water used by ancient civilizations, to the introduction of steam sterilization, which revolutionized infection control insurgical settings. Pioneers like Louis Pasteur and Joseph Lister laid the groundwork for modern aseptic techniques, significantly reducing postoperative infection rates. Today, sterilization practices are guided by authoritative organizations such as the Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO), which advocate for standardized protocols to ensure patient safety. The most prevalent sterilization methods include steam sterilization, ethylene oxide gas sterilization, and hydrogen peroxide vapor sterilization, each with specific applications and limitations. Steam sterilization remains the gold standard due to its efficacy and cost-effectiveness, but the complexity of modern surgical instruments presents ongoing challenges. Innovative heat-based sterilization techniques, particularly moist heat methods, have emerged as effective solutions for pathogen elimination. Recent advancements, such as pulsating vacuum technology, enhance steam penetration and improve sterilization outcomes for porous materials. However, challenges persist, including the variability in microbial resistance, the impact of biofilms on sterilization efficacy, and the compatibility of materials with various sterilization methods. The growing trend towards minimally invasive surgery further complicates sterilization efforts due to the intricate designs of instruments used. This study underscores the need for continuous updates to sterilization protocols, informed by the latest research and technological advancements, to ensure optimal patient outcomes and mitigate the risks associated with surgical procedures.